Battery preparation method and application for enhancing durability of proton ceramic fuel battery for preparing ethylene through ethane electrolysis
By using screen printing on the anode surface of the proton ceramic fuel cell and co-fired, a dense catalytic layer is formed, which solves the problems of high energy consumption of ethylene production and insufficient battery durability in traditional processes, and achieves a more efficient and environmentally friendly ethylene electrolysis process.
Patent Information
- Application Number
- CN202411667973.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-08
AI Technical Summary
The traditional steam cracking process consumes high energy and has serious environmental pollution. The existing proton ceramic electrochemical batteries have insufficient carbon deposit resistance and lack of durability during the process of ethylene electrolysis to make ethylene.
The catalyst layer is applied on the anode surface of the proton ceramic fuel cell by screen printing, and a dense catalytic layer is formed by co-firing treatment, thereby improving the resistance to carbon deposit and durability of the battery.
It significantly improves the anti-carbon deposit performance and durability of the battery, improves the efficiency and stability of ethylene electrolytics, and reduces production costs and environmental pollution.
Smart Images

Figure CN119776900A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a proton ceramic fuel cell for enhancing the durability of ethylene produced by ethane electrolysis and its application. Background Art
[0002] The traditional steam cracking process for ethylene production is the most energy-intensive process in the chemical industry, accounting for an estimated 60% of production costs and 2 / 3 of the manufacturing carbon footprint. It is recognized that the optimized methods for ethylene production by steam cracking of ethane or naphtha over the past few decades will be difficult to replace unless major breakthroughs are made in process intensification or catalyst science. Among various alternatives, protonic ceramic electrochemical cells (PCECs) have emerged as an efficient and environmentally friendly method for direct chemical production and energy conversion at intermediate temperatures (400-700°C). When ethane is converted to ethylene in PCEC, the hydrogen produced by the dehydrogenation reaction can be selectively removed from the product stream through the hydrogen oxidation reaction, forming protons at the anode and then transported to the cathode through the proton conductive electrolyte. To achieve efficient and stable ethylene production in PCEC, it is important to develop cells with high activity, selectivity and resistance to carbon deposition. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a battery that enhances the durability of a proton ceramic fuel cell used for ethane electrolysis to produce ethylene, that is, a catalyst layer BZCYYBNRu is brushed on the anode surface of a fuel cell (prepared by a casting method) by screen printing, and the two layers are co-fired to form a dense catalyst layer, thereby improving the battery's anti-carbon deposition performance.
[0004] A proton ceramic fuel cell anode comprises an anode and a catalyst loaded on the surface of the anode. The catalyst is used for converting alkanes into olefins.
[0005] The catalyst is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.05 Ru 0.05 O 3-δ The composite material composed of (BZCYYbNRu) and NiO has a weight ratio ranging from 5-10:1.
[0006] The anode material is Ni-BZCYYb.
[0007] A proton ceramic fuel cell comprises the above-mentioned anode, electrolyte and cathode.
[0008] The method for preparing the anode of the proton ceramic fuel cell comprises the following steps:
[0009] Step 1, obtaining an anode layer by a tape casting method;
[0010] Step 2, applying electrolyte on the surface of the anode blank obtained by the tape casting method by screen printing;
[0011] Step 3, coating the anode surface with a slurry containing a catalyst by screen printing;
[0012] Step 4: sintering to densify the anode layer and the catalyst layer.
[0013] The slurry also contains NiO powder, and the weight ratio of the catalyst to the NiO powder is in the range of 5-10:1, and the mass percentage of the total mass of the catalyst and the NiO powder in the slurry is 25-65%.
[0014] The solvent in the slurry is an alcohol solvent, and it also contains a dispersant and a thickener.
[0015] The sintering treatment is at 1450-1500℃ for 5-15h, and the heating rate is 0.5-5℃ / min.
[0016] The number of screen printing processes is 3-5 times.
[0017] The method for preparing ethylene by electrolysis of ethane comprises the following steps:
[0018] The proton ceramic fuel cell is first subjected to reduction treatment in a H2 atmosphere;
[0019] The anode contacts with a carrier gas containing C2H6, N2 and H2O to undergo a catalytic reaction to obtain a product gas containing C2H4.
[0020] The temperature condition of the catalytic reaction is 650-750°C.
[0021] Beneficial Effects
[0022] The invention relates to a method and application for changing the contact mode between a battery catalyst layer and an anode, enhancing the compactness of the catalyst layer, and improving the anti-carbon deposition performance and durability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a comparative IVP curve of 650℃-750℃ of the battery prepared with the catalytic layer tested in hydrogen atmosphere and in the atmosphere with C2H6 as the fuel gas;
[0024] Figure 2 (a) is a bar graph showing the conversion rate of C2H6 and the selectivity of C2H4 under OCV conditions. Figure 2 (b) To ensure the battery runs smoothly, add 300-500mA / cm 2Current, ensuring the conversion rate of C2H6 and the selectivity of C2H4 at each temperature point when the voltage is about 0.6V;
[0025] Figure 3 This is a comparison curve of the IVP at 650℃-750℃ of a comparison sample cell without a catalyst layer tested in an atmosphere with C2H6 as the fuel gas;
[0026] Figure 4 The results of the battery with catalytic layer and the battery without catalytic layer at 750℃ and 300mA / cm 2 IV stability curve obtained by operating at a current of;
[0027] Figure 5 This is a cross-sectional SEM image of the anode and electrolyte before and after the test of the battery with a catalyst layer;
[0028] Figure 6 This is the SEM image of the anode surface after the battery test with and without the catalyst layer;
[0029] Figure 7 This is the cross-sectional SEM image after the sprayed catalyst test. DETAILED DESCRIPTION
[0030] Example 1 Preparation of catalyst powder
[0031] This embodiment provides a bimetallic synergistic anode catalyst material Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.05 Ru 0.05 O 3-δThe preparation method comprises the following specific steps: 5.2268 g of barium nitrate, 0.7728 g of zirconium nitrate, 5.4712 g of cerium nitrate, 0.6894 g of yttrium nitrate, 0.8084 g of ytterbium nitrate, 0.2908 g of nickel nitrate, and 0.26145 g of ruthenium chloride are weighed and dissolved in a small amount of deionized water. 11.69 g of ethylenediaminetetraacetic acid and 16.81 g of hydrated citric acid are weighed as complexing agents in deionized water according to a molar ratio of ethylenediaminetetraacetic acid: hydrated citric acid: total metal ions of 1:2:1. After adding the solution containing the complexing agent to the solution containing the metal ions, an appropriate amount of ammonia water is added dropwise until the pH of the solution reaches 7, and then the solution is stirred under magnetic stirring until the water evaporates completely to obtain a gel-like substance. The gel-like substance is placed in an oven and calcined at 250°C for 5 hours to obtain the desired foam precursor. The precursor was placed in a high-temperature muffle furnace and calcined at 1100°C for 10 hours to obtain the desired powder. 1.76g of the obtained powder was mixed with 0.23g of NiO powder in a high-energy ball mill with ethanol as a solvent, and then dried in an oven at 60°C to obtain the desired catalyst powder.
[0032] Example 2 Preparation of screen printing paste
[0033] First, prepare the solvent of the slurry. Take 50g of pineol and add 4% ethyl cellulose. Heat and stir at low temperature for 24h to obtain the required solvent. Then take 2g of powder, add 2.4g of solvent and 0.2g of dispersant fish oil in a mortar, and grind by hand for 2-3h to obtain the slurry required for screen printing.
[0034] Preparation of cathode materials and single cell for low temperature proton ceramic fuel cell in Example 3
[0035] Take 9.8670g Ba(NO3)2, 8.0800g Fe(NO3)3·9H2O, 5.8206g Co(NO3)2·6H2O, 2.1466g Zr(NO3)4·5H2O and 1.9151g Y(NO3)3·6H2O, add appropriate amount of deionized water to dissolve, stir and heat to dissolve, and add complexing agent after the solution becomes clear and transparent; the complexing agent is 23g EDTA, 43g citric acid CA and 100mL ammonia water, stir until the solution is transparent, introduce it into the beaker with a glass rod and stir until the solution becomes clear and transparent. Ammonia water was added to the beaker to adjust the pH value of the solution to about 7. The solution was then stirred under magnetic stirring until the water was completely evaporated to obtain a gel-like substance. The gel was placed in a forced air drying oven and dried at a constant temperature of 180°C for more than 5 hours to obtain a precursor. The precursor was calcined at 1000°C for 5 hours with a heating rate of 5°C·min -1 , and obtain the desired cathode material powder.
[0036] The anode blank of the battery is obtained by tape casting. First, 120g NiO and 80g BZCYYb are weighed and placed in a previously prepared ball mill, and then 70g xylene, 50g ethanol and 6g fish oil are added to the planetary ball mill for high-speed ball milling for 12 hours. After the first ball milling is completed, 10g polyethylene glycol-400, 13g dioctyl phthalate, 2g cyclohexanone and 11.5g polyvinyl butyral are weighed and added to the ball mill, and the ball milling is continued in the planetary ball mill for 24h. Subsequently, the slurry with a certain viscosity is transferred to a vacuum degassing machine for degassing for 5min. Then the tape casting is carried out, in which the tape casting height is set to 2mm, and a part of the tape casting tape is placed in the air to dry naturally, and the other part enters the water container under the action of the conveyor belt for phase transformation treatment for 24h, and then dried in an oven at 60°C to obtain the Ni-BZCYYb tape casting sheet.
[0037] On the surface of the obtained anode body, an electrolyte layer was applied on one side by screen printing using the formula of Example 2, and a catalytic coating was applied on the other side to obtain a half-cell, which was first sintered at 1000°C for 5-10 hours for debinding, with a heating rate of 0.5-5°C / min. Then, the half-cell was sintered at 1450-1500°C for 5-15 hours, with a heating rate of 0.5-5°C / min, to make the cell dense.
[0038] The single cell adopts the BZCYYbNRu+NiO||Ni-BZCYYb||BZCYYb||BCFZY structure for electrochemical related tests. The porous BCFZY cathode is prepared by spraying. A certain amount of cathode powder is dissolved in a mixed solution of appropriate amounts of isopropanol, ethylene glycol and propylene glycol. The cathode is evenly dispersed with the help of a high-energy ball mill. The obtained BCFZY cathode slurry is evenly sprayed on the electrolyte side of the double-layer sheet preheated at 200°C under the impetus of inert gas. The battery after spraying 8 times is calcined at 1000°C-2h to obtain a single cell, and the heating rate is 5°C·min -1 , used for electrochemical testing in the temperature range of 650-750℃.
[0039] Comparative Example 1
[0040] The difference from Example 3 is that the catalyst layer is not printed on the anode side, and the other parameters are the same.
[0041] Comparative Example 2
[0042] The difference from Example 3 is that the catalyst layer is not printed on the anode side, the other parameters are the same, and the catalyst layer slurry is obtained by spraying on the anode side. The catalyst layer uses a certain amount of BZCYYbNRu catalyst powder dissolved in a mixed solution of appropriate amounts of isopropanol, ethylene glycol and propylene glycol, and the dispersion is uniformly ensured with the help of a high-energy ball mill.
[0043] Electrochemical testing
[0044] The prepared single cell was tested using a homemade fuel cell device at 650℃~750℃ with a temperature of 50℃. -1 Hydrogen was introduced into the anode side and the cathode side at a rate of 80 mL min -1 High-purity air was introduced for reduction, and the IV polarization curve of the reduced battery was collected using Digital Source Meter (Keithley 2420) in four-probe mode. The anode gas was then switched to 20% C2H6, 60% N2 and 20% water vapor, and the test was also performed using Digital Source Meter (Keithley 2420).
[0045] Conversion rate testing
[0046] When the anode gas inlet is switched to 20% C2H6, 60% N2 and 20% water vapor, the water vapor is liquid water quantitatively pumped in by a vaporizing pump, sent to a gas pipeline with a heating belt insulation through a carrier gas, and finally enters the reaction device. The product measured at the anode is dehydrated through a condensing device and then passed into a chromatogram to quantitatively analyze the composition of the product. The gas flow rate of the product is obtained by testing with a soap bubble flowmeter.
[0047] Stability test
[0048] The cells with and without catalyst layer were heated to 750℃ with 80ml / min H2, and after the reduction of the cells was completed, the anode atmosphere was switched to 20% C2H6, 60% N2 and 20% water vapor. 2 Rated current, record the voltage change curve IV.
[0049] Characterization results
[0050] Output power characterization
[0051] Figure 1 The IVP comparison curves of the prepared battery containing the catalyst layer under hydrogen atmosphere and under C2H6 as the fuel gas at 650℃·-750℃· are shown. At 750℃·, the output power of the battery under hydrogen is 985mW·cm -2 , which can achieve the general performance of a common anode-supported single cell without adding a catalyst layer under H2. After switching the anode intake to 20% C2H6, 60% N2 and 20% water vapor, the power at 750℃· was measured to be 449mW·cm -2 , 303mW·cm at 700℃ -2 , 200mW·cm at 650℃ -2 ,and Figure 3 The performance of the cell without a catalytic layer was measured when the anode gas was 20% C2H6, 60% N2 and 20% water vapor, that is, the power at 750℃ was 369mW·cm -2 , 294mW·cm at 700℃ -2 , 120mW·cm at 650℃ -2 Compared with conventional electrolyte-supported batteries, there is a slight improvement, and compared with conventional electrolyte-supported batteries, there is a significant improvement.
[0052] Conversion rate test characterization
[0053] The measured battery is under ocv operation condition. Figure 2 (a) C2H6 conversion at 750°C is 35.1%, and C2H4 selectivity is 78.4%, which is consistent with the increase of 450 mA / cm 2 The current measured when the battery voltage is about 0.6 Figure 2 (b) The C2H6 conversion rate is 37.6%, and the C2H4 selectivity is 95.4%. Compared with the previous step, both have been improved to a certain extent after adding current, and the same situation exists at other temperature points.
[0054] Stability testing characterization
[0055] Figure 4 The test shows that when the current is added to the battery without a catalytic layer and the battery is working, the voltage decays rapidly from 0.7V within 10 hours, while the voltage of the battery with a catalytic layer remains at around 0.73V within 80 hours. The stability of the battery has been greatly improved. This also proves that the addition of a catalytic layer can change the contact mode between the catalytic layer and the anode, enhance the density of the catalytic layer, and improve the battery's anti-carbon deposition performance and durability.
[0056] SEM characterization
[0057] Figure 5 Figures ab are cross-sectional views of the catalyst layer and the electrolyte before and after the battery test, and cd are SEM images of the cross-sections on both sides after the test. It can be seen from the figure that the catalyst layer is about 13μm after being brushed three times. A certain amount of pores are restored after the test to ensure the passage of hydrogen, and there is no sign of the catalyst layer falling off after the test.
[0058] Figure 6 Figure a is a SEM image of the anode surface after the test of a battery without catalyst. It can be seen from the image that there are many black substances agglomerated on the surface, which is the carbon deposition phenomenon of the battery. Figure 6 Figure b is a SEM image of the catalyst layer surface after the catalyst cell test. It can be seen that the catalyst layer surface is intact and no serious carbon deposition is found.
[0059] Figure 7This is the cross-sectional SEM image after the catalyst spray test. The battery is completely powdered and the cross-sectional boundary can no longer be seen. It can be seen that the battery obtained by the spraying method is basically consistent with the test results without catalyst, and the barrier effect on C2H6 gas is too weak.
Claims
1. A proton ceramic fuel cell anode, characterized in that: The invention comprises an anode and a catalyst supported on the surface of the anode, wherein the catalyst is used for converting alkane into olefin.
2. The proton ceramic fuel cell anode according to claim 1, characterized in that: The catalyst is Ba(Zr 0.1 Ce 0.7 Y 0.1 Yb 0.1 ) 0.9 Ni 0.05 Ru 0.05 O 3-δ The composite material composed of (BZCYYbNRu) and NiO has a weight ratio ranging from 5-10:
1.
3. The proton ceramic fuel cell anode according to claim 1, characterized in that: The anode material is Ni-BZCYYb.
4. A proton ceramic fuel cell, characterized in that: It includes the above-mentioned anode, electrolyte and cathode.
5. The method for preparing the anode of a proton ceramic fuel cell according to claim 4, characterized in that: The steps include: Step 2, obtaining an anode body by using a tape casting method; Step 2, coating the electrolyte layer on the surface of the anode blank by screen printing; Step 3, coating the surface of the anode powder with a slurry containing a catalyst by screen printing; Step 4: sintering to densify the anode layer and the catalyst layer.
6. The preparation method according to claim 5, characterized in that: The slurry also contains NiO powder, and the weight ratio of the catalyst to the NiO powder is in the range of 5-10:1, and the mass percentage of the total mass of the catalyst and the NiO powder in the slurry is 25-65%.
7. The preparation method according to claim 5, characterized in that: The solvent in the slurry is an alcohol solvent, and it also contains a dispersant and a thickener.
8. The preparation method according to claim 5, characterized in that: The sintering treatment is performed at 1450-1500°C for 5-15h, and the heating rate is 0.5-5°C / min; the number of screen printing processes is 3-5 times.
9. A method for preparing ethylene by electrolysis of ethane, characterized in that: The steps include: The proton ceramic fuel cell according to claim 4 is first subjected to reduction treatment in a H2 atmosphere; the anode is contacted with a carrier gas containing C2H6, N2 and H2O to perform a catalytic reaction to obtain a product gas containing C2H4.
10. The method for preparing ethylene by electrolysis of ethane according to claim 9, characterized in that: The temperature condition of the catalytic reaction is 650-750°C.
Citation Information
Patent Citations
Proton ceramic membrane fuel cell of composite structure and preparation
CN111224139A
Proton conductor fuel cell and preparation method thereof
CN113097512A
Ethylene and electric energy symbiotic solid oxide fuel cell and preparation method thereof
CN113299960A
Anode material of proton ceramic fuel cell, preparation method and application of anode material in direct ammonia fuel cell
CN116082028A
Proton ceramic fuel cell electrolyte material, spin-coating preparation method and application
CN117790854A